The use of oral health services by Brazilian elderly and associated factors: scoping review (Research, Society and Development, 2022)
Aim: To map and synthesize evidences on factors associated with the use of oral health services among Brazilian elderly. Methodology:  This is a scoping review guided by the guiding question “What factors are associated with the use of oral health services by the elderly in Brazil?”. The search for articles considered the Population, Concept and Context (PCC) strategy, by combining indexed terms and was carried out in the Medline/PubMed, Lilacs and SciELO databases, from May to July 2019. The discussion was based on theory by Andersen & Newman. Results: A total of 337 articles were identified, 12 met the review inclusion criteria. Studies are cross-sectional, published between 2007 and 2019. Factors associated with the use of oral health services were: age, gender, marital status, education, ethnicity / color / race, health knowledge, income, health insurance, region of the country - urban / rural area, symptoms, diagnosis of oral health condition and health behavior. Schooling, income and diagnosis of oral condition were the most evidenced factors in the studies. Conclusion: Different factors were associated with the use of oral health services by Brazilian elderly, with greater emphasis on sociodemographic and clinical need. Identifying barriers to unequal access to dental services may contribute to the reduction of oral disease among the elderly, with an accumulated need for treatment and rehabilitation.